An adaptation of the Framingham coronary heart disease risk function to European Mediterranean areas. Issue 8 (25th July 2003) - Marrugat, J; D'Agostino, R; Sullivan, L; Elosua, R; Wilson, P; Ordovas, J; Solanas, P; Cordón, F; Ramos, R; Sala, J; Masiá, R; Kannel, W B
Abstract : Aim: To determine whether the Framingham function accurately predicts the 10 year risk of coronary disease and to adapt this predictive method to the characteristics of a Spanish population. Method and Results: A Framingham function for predicting 10 year coronary deaths and non-fatal myocardial infarction was applied to the population of the province of Gerona, Spain, where the cumulated incidence rate of myocardial infarction has been determined since 1988 by a specific registry. The prevalence of cardiovascular risk factors in this region of Spain was established in 1995 by a cross sectional study on a representative sample of 1748 people. The number of cases estimated by the Framingham function for 10 year coronary deaths and non-fatal myocardial infarction was compared with that observed. The Framingham function estimated 2425 coronary heart disease cases in women and 1181 were observed. In men, 9919 were estimated and 3706 were observed. Recalibrating the Framingham equations to the event rate and the prevalence of the risk factors in Gerona led to estimates very close to the number of cases observed in Gerona men and women. Conclusions: The Framingham function estimates more than doubled the actual risk of coronary disease observed in north east Spain. After calibration, the Framingham function became an effective method of estimating the risk in this region with low coronary heart disease incidence.